Pro-environmental behavior, personality and emotional intelligence in adolescents: a systematic review - Lisboa, Paulo Vítor; Gómez-Román, Cristina; Guntín, Lidia; Monteiro, Ana Paula (Frontiers in Psychology, 2024)
Human behavior is a major contributor to environmental problems, hence the study of pro-environmental behavior remains an important task for psychology. In this context, it is crucial to understand the pro-environmental behavior of adolescents, as young people play a fundamental role in facilitating long-term changes in environmental consciousness and encouraging decision-makers to take action. However, little is currently known about the pro-environmental behavior of adolescents. Recently, there has been growing interest in examining the influence of personality traits and emotional intelligence on pro-environmental behavior. Thus, this systematic review was designed to enhance understanding of adolescent’s pro-environmental behavior by summarizing existing evidence on how it relates to personality and emotional intelligence. The findings reveal some associations with specific personality traits and dimensions of emotional intelligence, aligning with studies conducted on adults. However, further investigation of the interplay between multiple variables is needed to establish causality and deepen our understanding.